The Security Complexity of Iran–Saudi Arabia Relations in the Yemen Conflict, 2015–2023 - Baharmus, Nauval; Salma Sary Heryani (JURNAL TAPIS, 2025)
The conflict in Yemen epitomizes the geopolitical and ideological rivalry between Iran and Saudi Arabia two competing regional powers seeking to redefine the balance of influence in the Middle East. This study investigates why Yemen’s internal conflict has become prolonged and how regional power competition has entrenched instability across the region. Employing the Regional Security Complex Theory (RSCT) and a Security Interconnectedness approach, the research adopts a qualitative, library-based descriptive-analytical design. The data were collected through systematic review and content analysis of secondary sources, including peer-reviewed academic journals, United Nations Security Council and Panel of Experts reports (2015–2023), Gulf Cooperation Council (GCC) communiqués, and policy statements from Iranian and Saudi officials. The selection of documents followed relevance criteria linked to three RSCT dimensions: anarchic structure, regional polarity, and social construction. Findings show that Iran’s asymmetric intervention through support for the Houthis and Saudi Arabia’s coalition-based military response have transformed Yemen into a proxy arena linking regional conflicts in Syria, Iraq, and Lebanon. The 2023 Iran–Saudi rapprochement, while symbolically significant, has not yet restructured the underlying security logic of the region as mutual threat perceptions persist. The study contributes theoretically by expanding RSCT to incorporate identity and narrative as integral components of regional security, and empirically by providing updated insights into the post-2023 Middle Eastern order. Policy-wise, it underscores the need for inclusive, multi-level diplomacy that prioritizes human security and de-securitization of sectarian identities as prerequisites for sustainable peace in Yemen and the wider region.